Poland to America: Polish Immigrants in Chicago and their Reactions to the Start of World War I - Bruso, David (My University, 2017)
This research looks at Polish immigration to Chicago in the years leading up to World War I, with a focus on the immigrants' feelings towards the War. Poland was split up in 1795 between Russia, Austria, and the region known at the time as Prussia; which became Germany prior to the start of World War I. The country regained their national independence after the war in 1918. During this time there was a lot of coverage on what was going on in the Polish territory because it was the majority of the front line, and Poles that recently immigrated to Chicago were paying attention. Local Polish newspapers printed articles trying to rally support for their homeland, discussing how evil the Germans and Russians were and attempting to gather funds for the Polish National Alliance which represented the desire for an independent Polish nation. These papers help us to understand how Poles that moved to America reacted to what was happening in their old home. This work covers a brief history of Poland at the onset of WWI to help explain the large number of Polish immigrants that moved to Chicago during that time. There were a number of newspapers publishing stories about what was happening in Poland leading up to, and throughout the course of the war, and they help expose Polish sentiment while the mayhem in their home raged on. These papers were translated from their original Polish to English by the Chicago Public Library and published as part of the Chicago Foreign Press Survey.
USGZE AS333
Keywords: World War, 1914-1918; Immigrants -- History -- Chicago; Poland -- Emigration and immigration -- History; Polish immigration -- Cultural assimiliation -- Illinois